2004
DOI: 10.1515/jpm.2004.057
|View full text |Cite
|
Sign up to set email alerts
|

Waterbirths compared with landbirths: an observational study of nine years

Abstract: Waterbirths are associated with low risks for both mother and child when obstetrical guidelines are followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
117
6
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 20 publications
14
117
6
6
Order By: Relevance
“…Similar results were presented by other authors who suggested that in the water environment the rupture of membranes takes place later because of the smaller pressure differences, which potentially protects the child from infection [17,18,21]. Geissbuehler et al analysed 3617 medical histories of the development of neonates born in water and they did not notice either differences in the incidence of infections comparing to neonates after traditional delivery [15]. In our analysis only 1.4% of neonates born in water immersion was diagnosed with respiratory distress: two neonates with transient tachypnoea of the newborn (TTN).…”
Section: Ys K U Sj Asupporting
confidence: 74%
See 2 more Smart Citations
“…Similar results were presented by other authors who suggested that in the water environment the rupture of membranes takes place later because of the smaller pressure differences, which potentially protects the child from infection [17,18,21]. Geissbuehler et al analysed 3617 medical histories of the development of neonates born in water and they did not notice either differences in the incidence of infections comparing to neonates after traditional delivery [15]. In our analysis only 1.4% of neonates born in water immersion was diagnosed with respiratory distress: two neonates with transient tachypnoea of the newborn (TTN).…”
Section: Ys K U Sj Asupporting
confidence: 74%
“…However, we did not find any difference in the incidence of other perinatal traumas including cephalohaematoma, clavicle fracture, facial nerve trauma or adrenal haemorrhages. In the available literature only Geissbuehler et al compared perinatal injuries, noting a lower incidence of complications in the group of water-born children compared to the neonates born in traditional labour [15]. In the study the children's general condition evaluated by the Apgar score in the 1 st and 5 th minute of life did not vary significantly between the analysed groups of newborns.…”
Section: W Yn Ik Imentioning
confidence: 94%
See 1 more Smart Citation
“…In facilities that offer water births, adequate equipment should be provided for the protection and safety of the care provider, the woman, and her baby (i.e. effective infection prevention) [24].…”
Section: Water Birthmentioning
confidence: 99%
“…He concluded, "There is no credible evidence that water birth is a potential harm for either mothers or babies." He reported that most of the waterbirth studies have been done and published in Europe with large numbers in retrospective analyses (Alderdice et al, 1995;Geissbuehler, Stein, & Eberhard, 2004;Gilbert & Tookey, 1999;ZanettiDällenbach, Lapaire, Maertens, Holzgreve, Hösli, 2006). What has been published in the United States is largely anecdotal and has involved very small numbers of case reports from home-birth or birth center transfers into a neonatal intensive care unit (NICU; Bowden, Kessler, Pinette, & Wilson, 2003;Nguyen et al, 2002;Schroeter, 2004).…”
mentioning
confidence: 99%